AN OVERVIEW OF THE COST OF EQUITY CAPITAL AND INSTITUTIONAL OWNERSHIP IN INDONESIA - ade imam muslim (Jurnal Akuntansi, 2022)
The main issue experienced by developing countries is the high biaya modal ekuitas. Our study aims to explore institutional ownership in influencing the biaya modal ekuitas. For that purpose, we collected data through all issuers listed on the Indonesia Stock Exchange for the period 2016 to 2019. The total observations we collected were 984 observations. The research results provide empirical evidence that institutional ownership is not one factor that can reduce the biaya modal ekuitas. In other words, institutional ownership does not act as a monitoring effect that can control the efficiency and effectiveness and the disclosure made by the company so that it does not affect the high and low biaya modal ekuitas. Our research is expected to contribute to the development of the literature and fill the debate on institutional ownership in influencing the high and low biaya modal ekuitas.